Comparison of conventional and plant-extract disinfectant solutions on the hardness and color stability of a maxillofacial elastomer after artificial aging - Guiotti, Aimée Maria [UNESP]; Goiato, Marcelo Coelho [UNESP]; Dos Santos, Daniela Micheline [UNESP]; Vechiato-Filho, Aljomar José [UNESP]; Cunha, Bruno Guandalini [UNESP]; Paulini, Marcela Borghi [UNESP]; Moreno, Amália; De Almeida, Margarete Teresa Gottardo (Elsevier, 2016)
Statement of problem Silicone elastomers undergo physical and chemical degradation with disinfecting solutions. Phytotherapy may be a suitable solution for disinfection. However, its effect on the properties of the silicone material is unknown. Purpose The purpose of this in vitro study was to evaluate the effect of disinfection with conventional and plant-extract solutions and of artificial aging on the hardness and color stability of a facial silicone associated with pigments and an opacifier. Material and methods Four hundred specimens of silicone (MDX4-4210) were fabricated (5×6 mm). Two pigment shades and 1 dry opacifier were combined in the tested material, and 4 groups (n=10) were obtained: colorless (GI), colorless with opacifier (GII), medium pigment with opacifier (GIII), and black pigment with opacifier (GIV). Specimens were subjected to disinfection (30 days) using saline solution, water, and neutral soap (digital friction, 30 seconds), chlorhexidine 4%, Hydrastis canadensis, and Cymbopogon nardus extracts (immersion, 10 minutes). Shore A hardness (ASTM D2240) and color analyses were performed before and after disinfection. Specimens were then exposed to 1008 hours of artificial aging (ASTM 53) and subjected to final hardness and color readings. The results were analyzed with ANOVA and the Tukey significant difference test (α=.05). Results The opacifier increased the hardness (GII). For GII, the H. canadensis solution and the friction with water and soap promoted significantly reduced hardness; the friction also promoted a reduction in this property for GIV. The GIII was not affected after disinfection. A significant difference was found between the ΔE values of the specimens disinfected with H. canadensis, C. nardus, and chlorhexidine, and specimens subjected to saline solution and neutral soap. Conclusion The hardness of MDX4-4210 after the experimental procedure was considered clinically acceptable for facial prostheses. All groups showed clinically unacceptable color alterations regardless of the disinfecting solution.